2018
DOI: 10.1016/j.jesf.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient particulate matter on aerobic exercise performance

Abstract: Background/ObjectiveWintertime thermal inversions in narrow mountain valleys create a ceiling effect, increasing concentration of small particulate matter (PM2.5). Despite potential health risks, many people continue to exercise outdoors in thermal inversions. This study measured the effects of ambient PM2.5 exposure associated with a typical thermal inversion on exercise performance, pulmonary function, and biological markers of inflammation.MethodsHealthy, active adults (5 males, 11 females) performed two cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
17
1
2
Order By: Relevance
“…Similarly, Kubesch et al [12] found a positive association between increased traffic-related air pollution concentrations and increased FeNO levels, both at rest and after exercise. In contrast, a recent study by Wagner and Clark [19] did not show any dose-response relationships for PM 2.5 and FeNO in young healthy adults when exercising outdoors. Inconsistent outcomes of different studies may be partly a result of different exposure levels.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Similarly, Kubesch et al [12] found a positive association between increased traffic-related air pollution concentrations and increased FeNO levels, both at rest and after exercise. In contrast, a recent study by Wagner and Clark [19] did not show any dose-response relationships for PM 2.5 and FeNO in young healthy adults when exercising outdoors. Inconsistent outcomes of different studies may be partly a result of different exposure levels.…”
Section: Discussioncontrasting
confidence: 75%
“…However, in that case, the exercise lasted longer than in this study. Wagner and Clark [19] who examined direct post-exercise respiratory responses to brief exercise also did not observe any significant changes in FVC and FEV 1 . The strength of this study is the standardization of physical exercise.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Utah-based studies provide evidence that air pollution is associated with reduced lung function in susceptible populations. Studies of 16 healthy adults exposed to PM 2.5 below the federal 24 h health standard found no negative effects on respiratory function or aerobic performance after 20 min of heavy exercise [33,34], but multiple studies reported significant effects on lung function among children and adults with preexisting chronic obstructive pulmonary disease (COPD) [12,13,24]. Among fourth and fifth grade elementary students, 150 µg/m 3 increases in PM 10 were associated with a 3-6% decline in lung function [12].…”
Section: Lung Function and Performancementioning
confidence: 94%
“…Hence, it needs to be further clarified which exercise mode and intensity will bring better health effects under the AP context. Based on the acquired knowledge, it seems that doing one-bout aerobic exercise (a power bicycle) during an air quality index (AQI) ranking of “yellow” will not diminish exercise performance in healthy adults, nor has a negative effect on pulmonary function or biological health markers (Wagner and Clark, 2018 ). There is also evidence that the beneficial effects during exercise will be mitigated in PM 2.5 > 100 μg/m 3 (Tainio et al, 2016 ; Pasqua et al, 2018 ), which indicates that it should not be encouraged to exercise if PM 2.5 is greater than or equal to this value.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%